Katrina's Children: Evidence on the Structure of Peer Effects from Hurricane Evacuees - Imberman, Scott A; Kugler, Adriana D; Sacerdote, Bruce I (American Economic Review, 2012)
In 2005, Hurricanes Katrina and Rita forced many children to relocate across the Southeast. While schools quickly enrolled evacuees, families in receiving schools worried about the impacts on incumbent students. We find no effect, on average, of the inflow of evacuees on achievement in Houston. In Louisiana we find little impact on average and we reject linear-in-means models. Moreover, we find that student achievement improves with high achieving peers and worsens with low achieving peers. Finally, an increase in the inflow of evacuees raised incumbent absenteeism and disciplinary problems in Houston's secondary schools. (JEL I21, Q54)